2022
DOI: 10.1002/cti2.1428
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of Treg subsets distinguishes disease activity in ANCA vasculitis

Abstract: Objectives. T regulatory cells (Tregs) are a heterogeneous group of immunoregulatory cells that dampen self-harming immune responses and prevent the development of autoimmune diseases. In anti-neutrophil cytoplasmic autoantibody (ANCA) vasculitis, Tregs possess diminished suppressive capacity, which has been attributed to the expression of a FOXP3 splice-variant lacking exon 2 in T cells (FOXP3D2 CD4 + T cells). However, the suppressive capacity of Tregs varies between subsets. We evaluated the frequency of Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Research has shown that MPO + ANCA EGPA is associated with an increased count of three immunophenotypes in the Treg panel. In AAV, there is an increase in the count of Tregs 22 . However, during the progression stage, the expression of CD8+ CD25+ Tregs is downregulated and plays a crucial role in maintaining immune tolerance and regulating immune responses 48 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research has shown that MPO + ANCA EGPA is associated with an increased count of three immunophenotypes in the Treg panel. In AAV, there is an increase in the count of Tregs 22 . However, during the progression stage, the expression of CD8+ CD25+ Tregs is downregulated and plays a crucial role in maintaining immune tolerance and regulating immune responses 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have found that functional defects in Tregs are associated with various human autoimmune diseases 20,21 . In the case of AAV, a significant decrease in the proportion of activated Tregs was discovered, along with a reduction in their cellular functionality 22 . Research has indicated that heightened disease activity in EGPA is linked to decreased levels of Tregs 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T regulatory cells (Tregs), which dampen immune responses, are expanded in AAV patients in remission. Tregs subsets may distinguish disease activity with expanded CD103þ and CCR7þ subsets and decreased CXCR3þ subsets during active disease [8]. B-cell autoreactivity and autoantibody production are also important in AAV pathogenesis.…”
Section: Pathogenesismentioning
confidence: 99%